Buryak V.G., Buryak A.V., Drapak L.S., Buryak V.V. The patterns of change in contact length of tool and chip, shrinkage of shavings, tangentia component of the cutting force from the acoustic characteristics of tool materials during machining. - Буряк, В. Г.; Буряк, А. В.; Драпак, Л. С.; Буряк, В. В. (Problems of Tribology, 2018)
Analyze patterns of change in the contact length of tool and chip, shrink chip, tangentia component of the cutting force from the acoustic characteristics of tool materials during machining. Laws discusses the results of studies of changes of these parameters with velocity and acoustic impedance (complex acoustic impedance of the medium) that is calculated for the longitudinal wave propagating in the tool material. The obtained results are the initial data when using the assessment methodology performance cutting tools for the analysis of acoustic characteristics of the energy state of processed and tool materials with the use of differential equations the causal connection.